Determinants of stunting in children under five: a scoping review - Sihotang, Widya Yanti; Hulu, Victor Trismanjaya; Samosir, Frans Judea; Pane, Putri Yunita; Hartono, Hartono; Manalu, Putranto; Siagian, Masryna; Panjaitan, Hajijah I. L. (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Inadequate diet, socioeconomic condition, and maternal and child characteristics can damage stunted children under five's mental and physical development. As a result, they have difficulty developing physically and cognitively, have low intellectual abilities, are more susceptible to disease, and have less creativity and innovation. Objective: This study seeks to investigate and summarize the determinants of stunted children under five.Materials and Methods: The study used a scoping review method. The literature search was carried out on indexed databases of Scopus, PubMed, Google Scholar, Crossref, and Pro-Quest in English and Indonesian. There were 720 research articles, and 18 of them met the inclusion criteria. From the 18 journals, information was collected from the publication year 2015-2021. Relevant study articles related to the topic were analyzed qualitatively using NVIVO-12 Plus.Results: Our findings identify that maternal education, low birth weight (LBW), gender, exclusive breastfeeding, parental income, parental age, and child age are the dominant determinants of stunting among under-five children.Conclusion: Higher risk factors of stunting among children are parents' lack of knowledge, low family income, low nutrition, low level of mother's education, and lack of parents' supervision and parenting skills.